(untitled) (Revista de Biblioteconomia de Brasília, 1974)
FOSKETT, A. C. The Universal Decimal Classification: the history, present status and future prospects of a large general classification scheme. London: CLive Bingley, 1973. 171p. (ISBN 0-208-01195-1)